Income-related health inequality among rural residents in western China - Li, Chaofan; Tang, Chengxiang (Frontiers in Public Health, 2022)
Objective: Health equality has drawn much public attention in both developed and developing countries. China, the largest developing country, has implemented a new round of health system reform to improve health equality since 2009. This study aims to examine the magnitude and source of income-related health inequality in western rural region in China. Methods: The data was obtained from Survey of Rural Economic and Social Development in Western China conducted in 2014, in which 14,555 individuals from 5299 households in 12 provinces were included. Health outcome variables of interest were self-rated health status, prevalence of chronic disease and four-week illness, respectively. Concentration index was calculated to assess magnitude of income-related health inequality and nonlinear decomposition analysis was performed to identify the source of health inequality. Results: The Concentration indexes for poor self-rated health status, prevalence of chronic disease and four-week illness were -0.0898 (P<0.001), -0.0860 (P<0.001) and -0.1284 (P<0.001), respectively. Income and education were two main sources of health inequality, accounting for about 25%—50% and 15% contribution to the inequality. Ethnicity made less than 10% contribution to income-related health inequality, and New Rural Cooperative Medical Scheme contributed to less than 1%. Conclusion: This study found slight income-related health inequality among rural residents in western China, implied that although China has made substantial progress in economic development and poverty alleviation, health inequality in western rural region was still of concern to government. To achieve health equality further, Chinese government should not only strengthen health insurance scheme reimbursement to improve affordability of primary healthcare for residents in western rural regions, but implement health poverty alleviation policy targeting socioeconomically vulnerable population and ethnic minorities in future.